In the Relationship Between Change in Kyphosis and Change in Lordosis: Which Drives Which?. Issue 4 (May 2021) - Ang, Bryan; Lafage, Renaud; Elysée, Jonathan Charles; Pannu, Tejbir S.; Bannwarth, Mathieu; Carlson, Brandon B.; Schwab, Frank J.; Kim, Han Jo; Lafage, Virginie
Study Design: Retrospective single-center study. Objective: Investigate the effect of posterior instrumentation on the relationship between lordosis and kyphosis. Methods: Surgically treated patients with a minimum of 6 months of follow-up were analyzed. Asymptomatic volunteers served to show the normal anatomical relationship between thoracic and lumbar curves. Patients were stratified based on postoperative instrumentation: "Thoracic Fusion" = complete fusion of thoracic spine; "Lumbar Fusion" = complete fusion of lumbar spine; and "Complete Fusion" = fusion from sacrum to at least T5. Bivariate correlations and regression analysis were used to evaluate the relationship between change in thoracic kyphosis (ΔTK) and change in spinopelvic mismatch (ΔPI-LL; pelvic incidence-lumbar lordosis) before and after fusion. Analyses were repeated in "Lumbar Fusion" patients with flexible preoperative thoracic spines. Results: For asymptomatic volunteers, the natural anatomical relationship between TK and LL was found to be TK = 41% of LL ( r = 0.425, P < .001). A total of 153 of 167 adult spinal deformity patients were included (62 years old, 26.7 kg/m 2, 78% female). Mean follow-up was 11.5 ± 6.8 months. "Thoracic Fusion" group showed no alteration in the natural relationship between TK and LL (ΔTK = 39% ΔPI-LL), whereas "Lumbar Fusion" group had a reduction in reciprocal change (ΔTK = 34% ΔPI-LL) although a subanalysis of patients in the "Lumbar Fusion" group with flexible thoracic spines showed a marked compensation in reciprocal change with (ΔTK = 58% ΔPI-LL). Conclusion: The relationship between ΔTK and ΔPI-LL is dependent on level instrumented. "Thoracic Fusion" drives change in LL while this relationship is affected by TK's natural stiffness in "Lumbar Fusion" patients.